Screening and selection of Bacillus spp. for fermented corticate soybean meal production - Wongputtisin P. (2014)
Aims: To screen and select the Bacillus spp. from Tua-nao of northern Thailand for fermented corticate soybean meal (FCSBM) production. Methods and Results: After isolation of Bacillus spp. from Tua-nao was carried out, cellulase, hemicellulases (i.e., β-mannanase and xylanase) and phytase production by isolated Bacillus spp. were determined. B. subtilis isolate MR10 showed the highest β-mannanase, xylanase and phytase production at 280, 41 and 16 U g -1 substrate, respectively, while the highest cellulase production was found in TK8 at 25 U g -1 substrate. FCSBMs produced by single starter and mixed starter of both isolates showed the better properties than those of corticate soybean meal (CSBM), i.e., higher in soluble sugar, protein and phosphate content, smaller sugar molecules and better digestibility and absorbability than those of CSBM. Moreover, FCSBMs had no toxicity effect on mouse fibroblast cell line (3T3) but had an inhibitory effect on lung cancer cell line (CorL23). Conclusions: B. subtilis isolate MR10 and TK8 were selected for FCSBMs production because of their role as nutritional enhancer for CSBM and their safety. Significance and Impact of the Study: The results of this study were useful for FCSBM production process that can be applied as feed ingredient for monogastric animals. © 2012 The Society for Applied Microbiology.